Protective Cellular Immune Response Induction for Cutaneous Leishmaniasis by a New Immunochemotherapy Schedule - da Silva, Danielle A. M.; Santana, Fabiana R.; Katz, Simone; Garcia, Daniel M.; Teixeira, Daniela; Longo-Maugéri, Ieda M.; Barbiéri, Clara L. (Frontiers in Immunology, 2020)
The palladacycle complex DPPE 1.2 was previously shown to inhibit Leishmania (Leishmania) amazonensis infection in vitro and in vivo. The present study aimed to evaluate the effect of DPPE 1.2 associated with a recombinant cysteine proteinase, rLdccys1, and the adjuvant Propionibacterium acnes on L. (L.) amazonensis infection in two mouse strains, BALB/c and C57BL/6. Treatment with this association potentiated the leishmanicidal effect of DPPE 1.2 resulting in a reduction of parasite load in both strains of mice which was significantly higher compared to that found in groups treated with either DPPE 1.2 alone or associated with P. acnes or rLdccys1. The reduction of parasite load in both mice strains was followed by immunomodulation mediated by increase of memory TCD4+ and TCD8+ lymphocytes, IFN- levels and reduction of active TGF-β in treated animals. No infection relapse was observed one month after the end of treatment in mice which received DPPE 1.2 associated with rLdccys1 or rLdccys1 plus P. acnes in comparison to that exhibited by animals treated with DPPE 1.2 alone. Evaluation of serum levels of AST, ALT, urea, and creatinine showed no alterations among treated groups, indicating that this treatment schedule did not induce hepato or nephrotoxicity. These data indicate the potential use of this association as a therapeutic alternative for cutaneous leishmaniasis caused by L. (L) amazonensis.